Promoting Resilience in Youth through Mindfulness mEditation (PRYME): Study protocol for a randomized controlled trial investigating the effects of mindfulness training as add-on to care-as-usual on internalizing problems, mental illness development, and associated brain and cognitive processes in help-seeking youth - Maud Schepers; Paul Lagerweij; Dirk Geurts; Florian Krause; Hanneke den Ouden; Roshan Cools; Anne Speckens; Guusje Collin (BMC Psychiatry)
Abstract Background Internalizing problems, such as worrying, anxiety and low mood, are increasingly common in youth and may constitute an early stage of mental illness development. There is thus an urgent need for effective measures to address mental health complaints as they develop and to prevent progression into more serious mental illness. Enhanced understanding of early-stage mental illness development, associated cognitive and brain processes, and their amenability to early intervention is crucial to this effort. Mindfulness-based interventions offer an accessible intervention option with demonstrated positive effects on internalizing disorders such as depression. Furthermore, mindfulness-based interventions may modulate cognitive processes and brain activity patterns associated with internalizing disorders. This study aims to determine how early-stage mindfulness-based intervention impacts internalizing symptom development, associated cognitive and brain processes, and mental illness progression in help-seeking youth. Methods This longitudinal two-arm randomized controlled trial will be conducted in 155 help-seeking youth between 16 and 25 years of age. The investigational treatment, the Learning to Offset Stress program, is an adaptation of existing mindfulness-based programs. Developed for youth with internalizing problems, the training combines mindfulness exercises with mindful physical activity and yoga in 8 weekly 2-hour sessions. Participants are randomized to either Learning to Offset Stress program as an add on to care-as-usual, or care-as-usual-only. Assessments take place at baseline, end of treatment, and 2 months and 6 months after completion of treatment. The primary outcome is the level of internalizing problems measured with the internalizing subscale of the Adult Self Report questionnaire at end of treatment. Secondary outcomes include measures of self-compassion, rumination, experiential avoidance, and well-being. In addition, (functional) magnetic resonance imaging and computerized cognitive tasks are conducted at baseline and at end of treatment. Discussion The current randomized controlled trial aims to enhance our understanding of the trajectory of emerging mental illness, associated cognitive and brain processes, and their modulation by early-stage mindfulness-based intervention. Trial registration ClinicalTrials.gov NCT05916651. Registered on 23 June 2023.